Method for producing glass powder, conductive paste, and multilayer ceramic capacitor

JP7644214B1Active Publication Date: 2025-03-11NORITAKE MACHINE TECHNO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023215703
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-03-11
Estimated Expiration
2043-12-21

AI Technical Summary

Benefits of technology

【0008】 上記ガラス粉末では、該ガラス粉末の質量比を酸化物換算で上記のように制御している。これにより、ガラス粉末が溶融し、外部電極を形成する際、外部電極と積層チップとの十分な接着性を得ることが確認された。また、発明者の鋭意検討によれば、ガラス粉末中にBaOが含まれる場合、積層チップへの接着性能が低下することが分かった。したがって、上記ガラス粉末はBaOを実質的に含まない。これにより、積層チップへの接着性能の低下を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644214000001_ABST
    Figure 0007644214000001_ABST
Patent Text Reader

Abstract

The present invention aims to provide a general-purpose glass powder that provides sufficient adhesive performance for laminated chips that constitute various laminated ceramic capacitors, as well as related techniques. [Solution] The glass powder disclosed herein is a glass powder used in a conductive paste, and is characterized in that the glass powder has the following composition, calculated as oxide mass ratios: SiO2: 6 wt% to 18 wt%; B2O3: 18 wt% to 30 wt%; ZnO: 26 wt% to 47 wt%; Al2O3: 2 wt% to 17 wt%; CaO: 10 wt% to 25 wt%; and is substantially free of BaO.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a glass powder, a conductive paste, and a multilayer ceramic capacitor. [Background technology]

[0002] In recent years, multilayer ceramic electronic components such as multilayer ceramic capacitors (MLCCs), multilayer inductors, and multilayer piezoelectric elements (multilayer varistors) have been used in a wide range of fields. For example, an MLCC has a multilayer chip in which dielectric layers containing ceramic materials and internal electrode layers containing conductive materials are alternately stacked. External electrodes that connect to each of the multiple internal electrode layers are formed on the outside (e.g., side surfaces) of the multilayer chip. These external electrodes are formed, for example, by firing a conductive paste containing conductive particles and glass powder.

[0003] From the viewpoint of electrical conductivity reliability, external electrodes are required to have adhesive properties with laminated chips. In this regard, Patent Document 1 discloses a conductive composition for ceramic capacitor terminal electrodes, which is made by dispersing a glass frit in an organic vehicle, the glass frit containing elements constituting the glass at a predetermined ratio calculated as oxide. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 8-17140 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, as the demand for multilayer ceramic capacitors has increased, various performance requirements, such as higher capacitance and temperature characteristics, are being required. Therefore, the multilayer chips that make up multilayer ceramic capacitors are also diversifying in terms of the main components. Therefore, conductive pastes for external electrodes are required to have adhesive properties for a wide range of materials.

[0006] The technology disclosed herein has been created in view of the above, and aims to provide a versatile glass powder that provides sufficient adhesion performance for laminated chips constituting various laminated ceramic capacitors. In another aspect, the technology also aims to provide a conductive paste containing the glass powder and a method for manufacturing a laminated ceramic capacitor using the conductive paste. [Means for solving the problem]

[0007] The glass powder disclosed herein is a glass powder used in a conductive paste, and the glass powder has the following composition in terms of oxide mass ratio: The composition is characterized by containing SiO2: 6 wt% to 18 wt%; B2O3: 18 wt% to 30 wt%; ZnO: 26 wt% to 47 wt%; Al2O3: 2 wt% to 17 wt%; and CaO: 10 wt% to 25 wt%; and is substantially free of BaO.

[0008] In the above glass powder, the mass ratio of the glass powder is controlled as above in terms of oxide. As a result, it has been confirmed that sufficient adhesion between the external electrode and the laminated chip can be obtained when the glass powder is melted to form the external electrode. In addition, according to the inventor's intensive study, it has been found that when BaO is contained in the glass powder, the adhesive performance to the laminated chip is reduced. Therefore, the above glass powder does not substantially contain BaO. As a result, it is possible to suppress the deterioration of the adhesive performance to the laminated chip.

[0009] In a preferred embodiment of the glass powder disclosed herein, the glass powder is substantially free of alkaline earth metal oxides other than CaO.

[0010] In a preferred embodiment of the glass powder disclosed herein, the softening point of the glass powder is 500°C or higher and 650°C or lower.

[0011] In a preferred embodiment of the glass powder disclosed herein, the median diameter D 50 is 1 μm or more and 3 μm or less.

[0012] In a preferred embodiment of the glass powder disclosed herein, the glass powder contains 20 wt % or more of B2O3 in terms of mass ratio of oxide.

[0013] In a preferred embodiment of the glass powder disclosed herein, the glass powder contains 10 wt % or more Al2O3 in terms of mass ratio of oxide.

[0014] In another aspect of the technology disclosed herein, there is provided a conductive paste including the glass powder of the present disclosure, conductive particles, and a dispersion medium, which can provide sufficient adhesion to a laminated chip when the conductive paste is fired.

[0015] In a preferred embodiment of the conductive paste disclosed herein, the conductive particles are Cu particles.

[0016] In a preferred embodiment of the conductive paste disclosed herein, the conductive paste contains the glass powder in an amount of 4 wt % or more and 12 wt % or less when the entire conductive paste is taken as 100 wt %.

[0017] Furthermore, as another aspect of the technology disclosed herein, there is provided a method for manufacturing a multilayer ceramic capacitor. The method for manufacturing a multilayer ceramic capacitor disclosed herein includes a laminated chip preparation step of preparing a laminated chip, a paste application step of applying the conductive paste prepared in the paste preparation step to the surface of the laminated chip prepared in the laminated chip preparation step, and a firing step of firing the laminated chip to which the conductive paste has been applied. Here, the glass powder has the following composition in mass ratio calculated as oxide: The composition is characterized by containing SiO2: 6wt%-18wt%, B2O3: 18wt%-30wt%, ZnO: 26wt%-47wt%, Al2O3: 2wt%-17wt%, CaO: 10wt%-25wt%, and is substantially free of BaO. This allows for a multilayer ceramic capacitor with sufficient adhesion between the multilayer chip and the external electrodes to be obtained.

[0018] In a preferred embodiment of the method for producing a multilayer ceramic capacitor disclosed herein, the multilayer chip includes a dielectric layer containing a perovskite oxide as a main component.

[0019] In a preferred embodiment of the method for producing a multilayer ceramic capacitor disclosed herein, the perovskite oxide contains (CaSr)(TiZr)O3.

[0020] In a preferred embodiment of the method for producing a multilayer ceramic capacitor disclosed herein, the firing step is carried out at a firing temperature of 650° C. or higher and 850° C. or lower. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view for explaining the general configuration of an MLCC manufactured using a conductive paste containing glass powder according to one embodiment. [Diagram 2] FIG. 2 is a photograph of the evaluation electrode formed using Sample 1 after the scratch test. [Diagram 3] FIG. 3 is a photograph of the evaluation electrode formed using Sample 4 after the scratch test. [Figure 4] FIG. 4 is a photograph of the evaluation electrode formed using Sample 5 after the scratch test. [Diagram 5] FIG. 5 is a photograph of the evaluation electrode formed using Sample 12 after the scratch test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Preferred embodiments of the technology disclosed herein are described below. Matters other than those specifically mentioned in this specification and necessary for implementing the technology disclosed herein can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The technology disclosed herein can be implemented based on the contents disclosed in this specification and the technical common sense in the relevant field. In this specification, the expression "A to B" indicating a numerical range means "A or more and B or less."

[0023] [Glass powder] The glass powder disclosed herein is used for conductive paste applications. The glass powder disclosed herein melts during paste firing to become a liquid glass component. This liquid glass component fills the gaps between sintered bodies of conductive particles to densify the external electrodes and provide adhesive performance. The glass powder disclosed herein is characterized by including the following composition in terms of oxide mass ratios and substantially not including BaO. The glass powder disclosed herein will be described below. SiO2: 6wt%~18wt%; B2O3: 18wt%~30wt%; ZnO: 26wt%~47wt%; Al2O3: 2wt%~17wt%; CaO: 10wt%~25wt%;

[0024] (1) Composition of glass powder In this section, specific compositions of the glass powders disclosed herein will be described.

[0025] (a) Silicon oxide (SiO2) SiO2 is one of the components (glass skeleton components) that can form a glass skeleton by itself. As the ratio of SiO2 in the glass skeleton components increases, the thermal stability of the glass powder improves. SiO2 also has the function of increasing the chemical resistance of the glass powder. From this viewpoint, in the technology disclosed herein, the content ratio of SiO2 in the glass powder is set to 6 wt% or more. From the viewpoint of the thermal stability and chemical resistance of the glass powder, the content ratio of SiO2 is preferably 7.5 wt% or more, and more preferably 10 wt% or more. On the other hand, from the viewpoint that the viscosity becomes too high when melted when the content ratio is high, the content ratio of SiO2 in the glass powder is set to 18 wt% or less in the technology disclosed herein. From this viewpoint, the content ratio of SiO2 in the glass powder is preferably 16.5 wt% or less, and more preferably 12 wt% or less.

[0026] (b) Boron oxide (B2O3) B2O3 is one of the glass skeleton components. That is, the glass powder disclosed herein is a borosilicate glass containing SiO2 and B2O3 in the glass skeleton. In this borosilicate glass, as the proportion of B2O3 in the glass skeleton increases, the fluidity of the glass component after melting tends to improve, resulting in sufficient adhesive performance. From this perspective, in the technology disclosed herein, the content ratio of B2O3 in the glass powder is set to 18 wt% or more. From the perspective of further improving the fluidity of the glass component, the content ratio of B2O3 is preferably 20 wt% or more, more preferably 23 wt% or more, and particularly preferably 24 wt% or more. On the other hand, if the proportion of B2O3 becomes too high, the fluidity of the glass component increases too much, and the glass may seep out onto the electrode surface. This may result in the metal component being covered, which may inhibit conduction. Therefore, in the technology disclosed herein, the upper limit of the content ratio of B2O3 is set to 30 wt% or less. From the viewpoint of conduction reliability, the content of B2O3 in the glass powder is preferably 27 wt% or less, and more preferably 25 wt% or less.

[0027] (c) Zinc oxide (ZnO) ZnO is a component that can modify the glass skeleton (glass skeleton modifying component). This ZnO has the function of increasing the melting property of glass to adjust the viscosity of the glass component during firing, and also improving water resistance, thermal shock resistance, and the like. In the technology disclosed herein, from the viewpoint of improving water resistance, thermal shock resistance, and the like, the content ratio of ZnO in the glass powder is set to 26 wt% or more. From the viewpoint of improving water resistance, thermal shock resistance, and the like, the content ratio of ZnO in the glass powder is preferably 32 wt% or more, more preferably 35 wt% or more, and particularly preferably 40 wt% or more. This allows the formation of an external electrode with even greater durability. On the other hand, from the viewpoint of suppressing a decrease in adhesive performance due to excessively high fluidity of the glass component, the upper limit of the content ratio of ZnO is set to 47 wt% or less. From the viewpoint of suppressing a decrease in adhesive performance, the content ratio of ZnO in the glass powder is preferably 45 wt% or less, more preferably 43 wt% or less, and particularly preferably 41 wt% or less.

[0028] (d) Aluminum oxide (Al2O3) Al2O3 has a function of stabilizing the glass skeleton, and contributes to the chemical resistance and adhesive performance of the external electrode after firing. In the technology disclosed herein, the content ratio of Al2O3 in the glass powder is set to 2 wt% or more from the viewpoint of imparting more versatile adhesive performance to the external electrode after firing. Note that, from the viewpoint of forming an external electrode with more versatile adhesive performance, the content ratio of Al2O3 in the glass powder is preferably 2 wt% or more, more preferably 8 wt% or more, and particularly preferably 10 wt% or more. On the other hand, when the content ratio of Al2O3 in the glass powder increases, the fluidity of the glass component during firing tends to decrease, and the adhesive performance tends to decrease. Therefore, from the viewpoint of generating sufficient fluidity in the glass component at the early stage of firing, the upper limit of the content ratio of Al2O3 is set to 17 wt% or less. Note that, from the viewpoint of more suitably improving the fluidity of the glass component at the early stage of firing, the content ratio of Al2O3 is preferably 15 wt% or less, more preferably 14 wt% or less, and particularly preferably 12 wt% or less.

[0029] (e) Calcium oxide (CaO) CaO is a glass skeleton modifier and has the function of reducing the viscosity of the glass component after melting. That is, when the glass powder containing CaO is fired, a glass component with high fluidity that is easily diffused throughout the external electrode is generated. This greatly improves the denseness of the external electrode after firing, and can contribute to sufficient adhesive performance of the glass powder. In addition to the above-mentioned functions, CaO also has the function of improving chemical resistance and abrasion resistance. In the technology disclosed herein, the content ratio of CaO in the glass powder is preferably 10 wt% or more, more preferably 11 wt% or more, and particularly preferably 15 wt% or more. On the other hand, when the content ratio of CaO in the glass powder increases, the fluidity of the glass component becomes too high, which tends to cause a decrease in adhesive performance. In addition, from the viewpoint of more suitably suppressing the decrease in adhesive performance, the content ratio of CaO is preferably 25 wt% or less, more preferably 24 wt% or less, and particularly preferably 20 wt% or less.

[0030] (f) Barium oxide (BaO) The glass powder disclosed herein is characterized by being substantially free of barium oxide (BaO). Glass powders containing a large amount of BaO tend to have a large thermal expansion coefficient, which may result in a decrease in adhesive strength. Therefore, the glass powder according to the present disclosure does not substantially contain barium oxide (BaO). In this specification, "substantially free of BaO" refers to the absence of intentional addition of BaO. Therefore, in the case where a component that can be interpreted as BaO is contained in a small amount due to raw materials or a manufacturing process, etc., this is included in the concept of "substantially free of BaO" in this specification. For example, when the content of BaO in the glass powder is 0.01 wt% or less (preferably 0.005 wt% or less, more preferably 0.001 wt% or less, even more preferably 0.0005 wt% or less, and particularly preferably 0.0001 wt% or less), it can be said to be "substantially free of BaO".

[0031] (g) Alkaline earth metal oxides Although the effect of alkaline earth metal oxides other than calcium oxide (CaO) is smaller than that of barium oxide, there is a risk of reducing the adhesive strength to the glass powder. Therefore, in some preferred embodiments, the glass powder disclosed herein is preferably substantially free of alkaline earth metal oxides other than calcium oxide. In this specification, examples of "alkaline earth metal oxides other than calcium oxide" include magnesium oxide (MgO) and strontium oxide (SrO). In this specification, "substantially free of alkaline earth metal oxides other than calcium oxide" refers to the fact that alkaline earth metal oxides other than calcium oxide are not intentionally added. Therefore, when a component that can be interpreted as an alkaline earth metal oxide other than calcium oxide is contained in a small amount due to raw materials, manufacturing process, etc., it is included in the concept of "substantially free of alkaline earth metal oxides other than calcium oxide" in this specification. For example, when the content of alkaline earth metal oxides (excluding calcium oxide) in the glass powder is 0.1 wt% or less (preferably 0.05 wt% or less, more preferably 0.01 wt% or less, even more preferably 0.005 wt% or less, and particularly preferably 0.001 wt% or less), it can be said that the glass powder "substantially does not contain alkaline earth metal oxides other than calcium oxide."

[0032] (h) Other ingredients The above description is not intended to limit the composition of the glass powder disclosed herein to the above components. The glass powder disclosed herein may contain P2O5, Bi2O3, etc. as glass skeleton constituents other than SiO2 and B2O3. In addition, as glass skeleton modifiers, components other than BaO, such as Li2O, Na2O, K2O, TiO2, MnO, FeO, Fe2O3, Fe3O4, SnO, SnO2, V2O5, ZrO2, Nb2O5, CuO, Cu2O, La2O3, CeO2, etc. Although not intended to limit the technology disclosed herein, the total content ratio of these metal oxides is preferably 10 wt% or less, more preferably 7 wt% or less, even more preferably 5 wt% or less, and particularly preferably 3 wt% or less.

[0033] (2) Shape of glass powder, etc. Next, the shape of the glass powder and other details will be described.

[0034] (a) Median diameter Although not limiting the technology disclosed herein, the median diameter D 50 is preferably 10 μm or less, more preferably 7 μm or less, further preferably 5 μm or less, and particularly preferably 3 μm or less. 50 As the median diameter D of the glass powder becomes smaller, the glass powder melts more easily during paste firing, and adhesive performance tends to be fully exerted. 50 If the median diameter D of the glass powder is too small, the inorganic particles (conductive particles, glass powder) tend to aggregate with each other in the paste, and the viscosity of the paste tends to increase. 50 is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 0.7 μm or more, and particularly preferably 1 μm or more. In consideration of the adhesive performance of the external electrode after firing, it is preferable that the median diameter of the glass powder is smaller than the median diameter of the conductive particles. This allows fine glass powder to be placed in the gaps between the coarse conductive particles, making it easier for the glass component to fill the gaps between the sintered body of the conductive particles during firing.

[0035] (b) Aspect ratio Next, the shape of the glass powder is not particularly limited. The glass powder may be spherical or non-spherical (for example, rugby ball-shaped, columnar, needle-shaped, etc.). From the viewpoint of suppressing an increase in the viscosity of the paste, the glass powder is preferably spherical or approximately spherical. For example, the average aspect ratio of the glass powder is typically 1 to 2, preferably 1 to 1.5.

[0036] (c) Softening point The softening point of the glass powder is preferably 650°C or lower, more preferably 630°C or lower, even more preferably 610°C or lower, and particularly preferably 600°C or lower. This allows a glass component with suitable fluidity to be produced even in low-temperature firing, which can contribute to the adhesive performance of the external electrode after firing. On the other hand, from the viewpoint of suppressing a decrease in adhesive performance due to the glass component having too high fluidity, the softening point of the glass powder is preferably 500°C or higher, more preferably 520°C or higher, and particularly preferably 540°C or higher. Note that the "softening point" in this specification is the temperature at which glass begins to soften and deform under its own weight. Typically, the softening point is the temperature at which the "glass viscosity is about 10" measured in accordance with JIS R 3103-1 (2001). 7.6 The temperature at which the viscosity becomes dPa·s can be defined as the "temperature at which the viscosity becomes dPa·s."

[0037] [Conductive paste] Another aspect of the technology disclosed herein provides a conductive paste. The conductive paste of the present disclosure includes at least conductive particles, the glass powder having the above-described configuration, and a dispersion medium. Each component of the conductive paste disclosed herein will be described below.

[0038] 1.Conductive particles The conductive particles are materials that will be the main component of the external electrodes after firing. As the conductive particles, metal particles having the desired conductivity can be used without any particular limitation. Examples of such conductive particles include simple metals such as nickel (Ni), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), copper (Cu), ruthenium (Ru), rhodium (Rh), osmium (Os), iridium (Ir), aluminum (Al), and tungsten (W), as well as alloys containing these metals. In addition, the conductive particles may be any one of the above-mentioned metal materials used alone, or may be used in combination of two or more kinds. Among the above-mentioned conductive particles, Cu particles are particularly suitable as the main component of the external electrodes because they are inexpensive and have suitable conductivity.

[0039] The content of the conductive particles in the conductive paste is not particularly limited and can be adjusted as necessary. From the viewpoint of improving the electrical conductivity of the external electrode after firing, the content of the conductive particles is preferably 60 wt% or more, more preferably 65 wt% or more, and even more preferably 70 wt% or more. On the other hand, from the viewpoint of ensuring a certain content of glass powder and obtaining sufficient adhesiveness of the external electrode, the upper limit of the content of the conductive particles is preferably 90 wt% or less, more preferably 85 wt% or less, and even more preferably 80 wt% or less. In this specification, unless otherwise specified, the "content" means the mass ratio when the total mass of the conductive paste is 100 wt%.

[0040] The particle diameter of the conductive particles is not particularly limited, and any particle diameter that can be used in the field of conductive pastes can be used without any particular limitation. For example, the median diameter of the conductive particles may be 0.1 μm or more, 0.25 μm or more, 0.5 μm or more, or 1 μm or more. The median diameter of the conductive particles may be 50 μm or less, 25 μm or less, or 10 μm or less. In this specification, the "median diameter" is the particle diameter (volume equivalent sphere diameter) that corresponds to 50% of the cumulative value from the small particle diameter side in the volume-based particle size distribution based on the laser diffraction scattering method.

[0041] The shape of the conductive particles is not particularly limited. For example, the shape of the conductive particles may be spherical or non-spherical. The non-spherical shape may be, for example, plate-like, scale-like, flake-like, or amorphous. From the viewpoint of facilitating an increase in the packing density of the conductive particles, for example, spherical conductive particles having an aspect ratio of 1.2 or less, preferably 1.15 or less, for example, 1.1 or less, can be preferably used. From the viewpoint of facilitating an increase in the contact area of ​​the conductive particles, for example, non-spherical conductive particles having an aspect ratio of more than 1.2, preferably 1.3 or more, 1.5 or more, for example, 1.7 or more, more preferably 2 or more, can be used. From the viewpoint of synergizing the above effects, the conductive particles may be a mixture of spherical and non-spherical particles. As a result, when the solvent is removed from the paste by drying, the multiple conductive particles are in favorable contact with each other, and the electrical conductivity of the conductive film can be increased. In addition, the "average aspect ratio" in this specification is calculated based on electron microscope observation. Specifically, the aspect ratio is the ratio (b / a) of the length of the long side (b) to the length of the short side (a) when a rectangle is drawn circumscribing the particle in an electron micrograph, and the average aspect ratio is the arithmetic mean value of the aspect ratios obtained for 100 particles.

[0042] The content of glass powder in the conductive paste is preferably adjusted as necessary. Note that as the content of glass powder increases, the adhesive performance of the external electrode after firing can be favorably obtained. From this viewpoint, when the total mass of the conductive paste is taken as 100 wt%, the content of glass powder is preferably 4 wt% or more, more preferably 6 wt% or more, and even more preferably 7.5 wt% or more. On the other hand, in consideration of suppressing the deterioration of adhesive performance due to glass floating, the upper limit of the content of glass powder is preferably 12 wt% or less, more preferably 10 wt% or less.

[0043] 3.Dispersion medium The dispersion medium is a liquid medium that disperses the above-mentioned powder materials (conductive particles, glass powder, etc.). The detailed components of the dispersion medium are not particularly limited, and any conventionally known dispersion medium that can be used for preparing a conductive paste can be used. In addition, since the dispersion medium is a component that is assumed to disappear by drying and firing, it is preferable that the boiling point is about 150°C or more and 300°C or less (for example, about 170°C or more and 270°C or less).

[0044] An example of the dispersion medium is an organic dispersion medium (non-aqueous dispersion medium). Examples of such organic dispersion mediums include alcohol-based solvents such as methanol, sclareol, citronellol, phytol, geranyl linalool, texanol, benzyl alcohol, phenoxyethanol, 1-phenoxy-2-propanol, terpineol, dihydroterpineol, isoborneol, butyl carbitol, and diethylene glycol; ester-based solvents such as terpineol acetate, dihydroterpineol acetate, isobornyl acetate, carbitol acetate, and diethylene glycol monobutyl ether acetate; and mineral spirits. Among these, alcohol-based solvents (e.g., dihydroterpineol) can be preferably used.

[0045] The content of the dispersion medium is preferably adjusted appropriately in consideration of the workability when applying the conductive paste. Since the workability when applying the paste may vary depending on the application means, the content of the dispersion medium is not limited to a specific value. As an example, when screen printing is used as the application means, the content of the dispersion medium can be adjusted to within the range of 5 wt% to 20 wt% (preferably 10 wt% to 15 wt%).

[0046] 4. Other Additives The conductive paste disclosed herein may contain, without particular limitation, additives that are conventionally known and can be used in this type of conductive paste, as long as they do not significantly impair the effect (adhesive performance) of the technology disclosed herein. For example, the conductive paste may contain binders, dispersants, thickeners, plasticizers, pH adjusters, stabilizers, leveling agents, defoamers, antioxidants, sintering aids, preservatives, colorants (pigments, dyes, etc.), etc.

[0047] For example, the binder (binding agent) is an additive that contributes to improving the fixation when the paste is applied to the laminated chip and the bonding between the conductive particles. In addition, the binder is preferably a material that disappears during firing, like the dispersion medium. Therefore, the binder is preferably an organic binder (typically an organic compound with a burnout temperature of 500° C. or less). The specific components of the binder in the conductive paste disclosed herein are not particularly limited, and conventionally known binders can be used without particular limitations. Examples of such binders include organic polymer compounds such as rosin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyvinyl acetal-based resins, acrylic resins, urethane-based resins, epoxy-based resins, phenol-based resins, polyester-based resins, and ethylene-based resins. Although it cannot be generalized because it depends on the combination with the above-mentioned dispersion medium, among these organic compounds, cellulose-based resins, polyvinyl alcohol-based resins, polyvinyl acetal-based resins, acrylic resins, and the like are suitable as binders. The binder may be any one of the above-mentioned organic compounds, or may be used in combination of two or more. The binder may be a copolymer or block copolymer obtained by copolymerizing these organic compounds. The binder content is preferably adjusted appropriately so that suitable fixability can be exhibited. For example, the binder content is preferably 1 wt% or more, more preferably 1.5 wt% or more, even more preferably 2 wt% or more, and particularly preferably 2.5 wt% or more. On the other hand, from the viewpoint of preventing binder residue after firing, the binder content is preferably 10 wt% or less, more preferably 9 wt% or less, even more preferably 8 wt% or less, and particularly preferably 7.5 wt% or less.

[0048] The dispersant is an additive that suppresses the aggregation of inorganic particles (conductive particles, glass powder, etc.) in the paste. Specifically, the dispersant has a function of stabilizing the solid-liquid interface between the inorganic particles and the dispersion medium and preventing the aggregation of the inorganic particles. Therefore, the glass powder in the paste can be uniformly dispersed, and the adhesive performance of the glass powder can be more suitably exhibited. The type of dispersant is not particularly limited, and a conventionally known dispersant can be appropriately selected as necessary. An example of such a dispersant is an anionic dispersant. An anionic dispersant has excellent adsorption power to inorganic particles, so that the inorganic particles can be appropriately dispersed for a long period of time. An example of such an anionic dispersant is a carboxylic acid dispersant. Specific examples of such a carboxylic acid dispersant include stearic acid, oleic acid, myristic acid, palmitic acid, linoleic acid, lauric acid, and linolenic acid. The conductive paste may contain two or more dispersants. The content of such a dispersant is preferably adjusted within the range of 0.05 wt % to 5 wt % (preferably 0.1 wt % to 1 wt %, and more preferably 0.1 wt % to 0.5 wt %).

[0049] [Conductive paste applications] The conductive paste disclosed herein has been described above. The conductive paste having the above configuration is used in the manufacture of multilayer ceramic electronic components such as multilayer ceramic capacitors (MLCCs), and is suitably used as an external electrode paste for forming external electrodes of the multilayer ceramic electronic components.

[0050] [Multilayer ceramic capacitors (MLCC)] Hereinafter, a multilayer ceramic capacitor (MLCC) will be described as an example of an application of the conductive paste disclosed herein. Fig. 1 is a schematic cross-sectional view for explaining the configuration of an MLCC. As shown in Fig. 1, a multilayer ceramic capacitor (MLCC) 1 typically includes a laminated chip 10 and external electrodes 40 formed on a pair of opposing end faces of the laminated chip 10.

[0051] The laminated chip 10 has a plurality of internal electrode layers 30 laminated with dielectric layers 20 interposed therebetween. In an actual MLCC, the dielectric layers 20 are integrated to such an extent that the junction boundaries between them are not visible. The laminated chip 10 is formed by applying a conductive paste, which is a precursor of the internal electrode layers 30, to the surface of a ceramic green sheet, which is a precursor of the dielectric layers 20, and then drying and firing them at the same time. Here, a part of the internal electrode layers 30 is exposed on the end faces of the laminated chip 10 (the left and right ends in FIG. 1).

[0052] The dielectric layer 20 is typically composed of a laminated sintered body (ceramic base) of ceramic green sheets containing a ceramic dielectric. The dielectric layer 20 may be one or more of various ceramic dielectrics in conventionally known MLCCs, depending on the application. In some preferred embodiments, the dielectric layer 20 may be preferably composed of a perovskite oxide as a main component. In this specification, the term "perovskite oxide" refers to a composition represented by the general formula ABO3. Here, A in the formula indicates an element occupying the A site of the perovskite crystal structure, and B in the formula indicates an element occupying the B site of the perovskite crystal structure. In this specification, the main component refers to the component with the highest content in the entire dielectric layer 20, and typically the main component occupies 50 mass% or more of the dielectric layer 20, preferably 70 mass% or more, and more preferably 90 mass% or more.

[0053] Examples of perovskite oxides include BaTiO3 (barium titanate), (CaSr)(TiZr)O3 (hereinafter also referred to as "CSTZ"), SrTiO3 (strontium titanate), CaTiO3 (calcium titanate), MgTiO3 (magnesium titanate), (Bi 1 / 2 Na 1 / 2 )TiO3 (bismuth sodium titanate, BNT), Pb(Zr x Ti 1―x )O3 (lead zirconate titanate, PZT), TiZnO3 (zinc titanate), Ba(Mg 1 / 3 Nb 2 / 3)O3 (barium magnesium niobate), CaZrO3 (calcium zirconate), Ba(ZrTi)O3 (barium zirconate titanate, BZT), etc. Among them, as the perovskite oxide, barium titanate or CSTZ can be preferably adopted, and CSTZ can be more preferably adopted.

[0054] However, the components of the dielectric layer 20 are not limited to these, and may be other components than perovskite oxide components, such as TiO2 (titanium dioxide, rutile), Ti3O5 (titanium pentoxide), HfO2 (hafnium oxide), ZrO (zirconium oxide), Al2O3 (aluminum oxide), 2MgO.SiO2 (forsterite), NbO (niobium oxide), BaNd2Ti5O 14 Other metal oxides such as (barium neodymium titanate), rare earth element oxides, etc. may also be used.

[0055] In addition, it is known to those skilled in the art that the perovskite crystal structure generally exhibits ionic conductivity due to oxygen deficiency caused by charge compensation due to the influence of the environmental temperature, atmosphere, etc. In this case, if the amount of oxygen deficiency is δ, the perovskite crystal structure can be expressed by the general formula ABO 3-δ and δ typically satisfies 0≦δ≦1. In the technology disclosed herein, such deviation in composition in oxides having a perovskite crystal structure is naturally permitted. Similarly, it is known that the perovskite crystal structure is robust to chemical solid solution and can be partially substituted by ions of different valences or sizes, and it is also known that, for example, the ratio of A-site elements to B-site elements can deviate from 1:1. In this specification, the ratio of A-site elements to B-site elements is not limited to being strictly 1:1 within the scope of the essence of the technology disclosed herein. For example, the ratio of A-site elements to B-site elements is permitted to deviate by about 1:0.95 to 1.05 (typically about 1:0.98 to 1.02).

[0056] The internal electrode layer 30 in FIG. 1 can adopt the structure and materials of a conventionally known MLCC without any particular restrictions, and is not a limiting factor of the technology disclosed herein, so a detailed description will be omitted.

[0057] In this MLCC 1, a pair of external electrodes 40 are provided on the side surfaces of a laminated chip 10 consisting of a dielectric layer 20 and an internal electrode layer 30. As an example, the internal electrode layers 30 are connected to different external electrodes 40 alternately in the stacking order. This results in a small-sized, large-capacity MLCC in which a capacitor structure consisting of a dielectric layer 20 and a pair of internal electrode layers 30 sandwiching the dielectric layer 20 is connected in parallel. In addition, although not shown in the figure, a metal plating layer is formed on the surface of the external electrode 40.

[0058] Incidentally, in the MLCC 1, in order to maintain the reliability of conduction between the internal electrode layer 30 and the external electrode 40, adhesion between the external electrode 40 and the laminated chip 10 (more specifically, between the external electrode 40 and the dielectric layer 20) is required. The external electrode 40 of this MLCC 1 is formed by firing the conductive paste disclosed herein. As described above, the external electrode 40 formed using the conductive paste disclosed herein has excellent adhesion. For this reason, an MLCC 1 with high conductivity reliability can be obtained in which the external electrode 40 and the laminated chip 10 are firmly bonded (joined).

[0059] The MLCC has been described above as an example of the application of the conductive paste containing the glass powder disclosed herein. The application of the conductive paste containing the glass powder disclosed herein is not limited to the above-mentioned MLCC. Other examples of multilayer ceramic electronic components for which the conductive paste containing the glass powder disclosed herein can be used include multilayer inductors and multilayer piezoelectric elements (multilayer varistors). These electronic components may also require adhesive performance between the external electrodes and the multilayer chips. In response to this, the conductive paste containing the glass powder disclosed herein can contribute sufficient adhesive performance of the external electrodes. Therefore, by using the conductive paste containing the glass powder disclosed herein, it is possible to manufacture multilayer inductors, multilayer varistors, etc. with high electrical conductivity reliability.

[0060] [Manufacturing method of multilayer ceramic capacitors] Another aspect of the technology disclosed herein provides a method for manufacturing a multilayer ceramic capacitor (MLCC). The manufacturing method includes at least a paste preparation step, a paste application step, and a firing step. In addition to the above steps, the manufacturing method for an MLCC disclosed herein may further include other steps at any stage, and the other manufacturing processes may be the same as conventional ones.

[0061] 1.Paste preparation process In this process, a conductive paste containing glass powder, conductive particles, and a dispersion medium is prepared. The glass powder of the conductive paste prepared in this process is characterized by having the following composition in mass ratios calculated as oxides and being substantially free of BaO. This allows for the stable formation of external electrodes with versatile adhesive properties. SiO2: 6wt%~18wt%; B2O3: 18wt%~30wt%; ZnO: 26wt%~47wt%; Al2O3: 2wt%~17wt%; CaO: 10wt%~25wt%;

[0062] The conductive paste prepared in this step may have the above-mentioned configuration except that it contains the glass powder of the above-mentioned composition, and as this has already been explained, a duplicate explanation will be omitted.

[0063] When preparing a conductive paste in this process, conductive particles and glass powder may be added to a dispersion medium and stirred using a conventional stirring and mixing device (e.g., a roll mill, a magnetic stirrer, a planetary mixer, a disperser, etc.).

[0064] 2. Stacked chip preparation process In this process, the laminated chip 10, which is the main body of the MLCC 1, is prepared. In this process, when preparing the laminated chip 10, for example, first, a ceramic green sheet is prepared as a base material. In one example, a ceramic material as a dielectric material, a binder, an organic solvent, etc. are stirred and mixed to prepare a paste for forming a dielectric layer. Next, the prepared paste is spread on a carrier sheet by a doctor blade method or the like to form a plurality of unfired ceramic green sheets. A predetermined pattern is applied to the plurality of molded ceramic green sheets so as to have a desired thickness (for example, submicron to micron level) to form a conductor film on each of them. This conductor film is a part that becomes an internal electrode layer after firing. In this way, a plurality of ceramic green sheets with unfired conductor films (for example, hundreds to thousands) are prepared, and then these are stacked and pressure-bonded. In this way, an unfired laminated chip is produced.

[0065] Next, the unsintered laminated chip produced above is sintered under appropriate heating conditions (for example, at a temperature of about 1000 to 1300°C). This allows the laminated chip to be co-fired (baked) and integrally sintered. In this manner, a laminated chip 10 in which a large number of dielectric layers 20 and internal electrode layers 30 are alternately stacked can be obtained. However, this process is not limited to such a means, and it can also be prepared by obtaining a laminated chip that has already been sintered.

[0066] The laminated chip 10 prepared in this step can be one having a dielectric layer used in the conventionally known MLCC as described above. In some embodiments, a laminated chip having a dielectric layer mainly composed of perovskite oxide can be preferably adopted. Since the conductive paste of the present disclosure contains glass powder having the above composition, an external electrode 40 having sufficient adhesive performance is formed on the laminated chip 10 in the subsequent firing step. Therefore, even when a laminated chip 10 having a dielectric layer mainly composed of perovskite oxide is adopted, it is possible to provide an MLCC 1 having excellent electrical reliability in which the external electrode 40 and the laminated chip 10 are bonded with sufficient strength. In addition, as the dielectric layer mainly composed of perovskite oxide, barium titanate or CSTZ can be preferably adopted, and CSTZ can be more preferably adopted.

[0067] 3. Paste application process In this step, the conductive paste is applied to a part of the surface (e.g., the side surface) of the prepared laminated chip. Examples of methods for applying the conductive paste include a dip coating method, a dispenser supply method, a printing method such as screen printing, gravure printing, offset printing, and inkjet printing, and a spray coating method. When forming an external electrode of an MLCC, the dip coating method is more suitable.

[0068] 4. Firing process In this process, the laminated chip coated with the conductive paste is fired at a predetermined temperature. This forms an MLCC having the laminated chip and external electrodes. In this process, the conductive particles in the paste are sintered to form a porous fired body, and the glass powder is melted and filled into the voids of the fired body. At this time, the glass powder of the conductive paste disclosed herein is configured to have a predetermined ratio of SiO2, Al2O3, B2O3, ZnO, and CaO, and is substantially free of BaO. This allows the glass components to be appropriately diffused throughout the external electrodes, forming external electrodes with sufficient adhesive performance. The firing temperature (maximum firing temperature) in this process is preferably 650°C to 850°C, and more preferably about 670°C to 800°C.

[0069] As described above, specific aspects of the technology disclosed herein include those described in the following sections.

[0070] [Item 1] A glass powder used in a conductive paste, The glass powder has the following composition in terms of oxide mass ratio: SiO2: 6wt%~18wt%; B2O3: 18wt%~30wt%; ZnO: 26wt%~47wt%; Al2O3: 2wt%~17wt%; CaO: 10wt%~25wt%; and is substantially free of BaO; Glass powder.

[0071] [Item 2] 2. The glass powder according to item 1, wherein the glass powder is substantially free of alkaline earth metal oxides other than CaO.

[0072] [Item 3] 3. The glass powder according to item 1 or 2, wherein the softening point of the glass powder is 500° C. or higher and 650° C. or lower.

[0073] [Item 4] The median diameter D of the above glass powder 50 4. The glass powder according to any one of items 1 to 3, wherein the average particle size is 1 μm or more and 3 μm or less.

[0074] [Item 5] 5. The glass powder according to any one of items 1 to 4, wherein the glass powder contains 20 wt % or more of B2O3 in terms of mass ratio of oxide.

[0075] [Item 6] 6. The glass powder according to any one of items 1 to 5, wherein the glass powder contains 10 wt % or more of Al2O3 in terms of mass ratio of oxide.

[0076] [Item 7] A glass powder according to any one of items 1 to 6, conductive particles, and a dispersion medium. Conductive paste.

[0077] [Item 8] 8. The conductive paste according to item 7, wherein the conductive particles are Cu particles.

[0078] [Item 9] 9. The conductive paste according to item 7 or 8, wherein the glass powder is contained in an amount of 4 wt % or more and 12 wt % or less when the entire conductive paste is taken as 100 wt %.

[0079] [Item 10] A paste preparation step of preparing a conductive paste containing glass powder, conductive particles, and a dispersion medium; a laminated chip preparation step of preparing a laminated chip; a paste application step of applying the conductive paste prepared in the paste preparation step to a surface of the laminated chip prepared in the laminated chip preparation step; a firing step of firing the laminated chip to which the conductive paste is applied; A method for producing a multilayer ceramic capacitor, comprising: The glass powder has the following composition in terms of oxide mass ratio: SiO2: 6wt%~18wt%; B2O3: 18wt%~30wt%; ZnO: 26wt%~47wt%; Al2O3: 2wt%~17wt%; CaO: 10wt%~25wt%; and is substantially free of BaO; A method for manufacturing a multilayer ceramic capacitor.

[0080] [Item 11] The laminated chip includes a dielectric layer mainly composed of a perovskite oxide. Item 11. A method for producing a multilayer ceramic capacitor according to item 10.

[0081] [Item 12] The perovskite oxide includes (CaSr)(TiZr)O3. Item 12. A method for producing a multilayer ceramic capacitor according to item 11.

[0082] [Item 13] 13. The method for producing a multilayer ceramic capacitor according to any one of items 10 to 12, wherein the firing step is carried out at a firing temperature of 650° C. or higher and 850° C. or lower.

[0083] [Test example] Next, test examples related to the technology disclosed herein will be described. Note that the test examples described below are not intended to limit the technology disclosed herein.

[0084] <Preparation of glass powder> (1) Sample 1 to Sample 12 Here, the glass powder (median diameter D 50 The compositions of the glass powders of Samples 1 to 12 are shown in Table 1.

[0085] <Evaluation of glass powder> 1-1. Evaluation of adhesive strength In this test, the adhesive strength of the glass powder in each of the samples prepared above was evaluated.

[0086] (1) Preparation of test specimens First, plate-shaped Cu particles (median diameter D 50A glass powder of each example was prepared by pressing the Cu particles at a ratio of 11 wt% of external addition. Then, a button-shaped pellet of φ15 mm×1.5 mm was prepared by press molding. Next, a mixture of CSTZ powder and binder (polyvinyl alcohol aqueous solution) was press molded and fired at 1280° C. for 2 hours in an air atmosphere. This prepared a flat substrate (hereinafter referred to as CSTZ substrate) with dimensions of 26 mm×26 mm×1.3 mm. Then, the pellet obtained above was placed on the CSTZ substrate prepared above, and firing treatment was performed at 730° C. for 30 minutes in a nitrogen atmosphere. This obtained a test piece in which the pellet was fired on the substrate.

[0087] (2) Adhesive strength test Using a Nordson DAGE 4000 universal bond tester, a load was applied to the pellets under room temperature conditions, and the strength (adhesive strength) was measured when the pellets peeled off. Specifically, the substrate portion of the test piece prepared above was fixed to the tester, and a shear tool was used to apply a shear force to the pellets in a direction horizontal to the bonding surface. The strength when the pellets peeled off from the substrate was taken as the adhesive strength (N). This evaluation was performed for each sample, N=3, and the arithmetic average value (Ave. value) of the adhesive strength was calculated. Then, for each sample, those with an Ave. value of more than 20N were deemed to have passed. The results are shown in Table 1. Note that a higher adhesive strength value indicates that the pellets (i.e., glass powder) have better adhesive performance (i.e., are less likely to peel off).

[0088] [Table 1]

[0089] As shown in Table 1, in Samples 5 to 7, in which BaO was contained in the glass powder, sufficient adhesive performance was not obtained with respect to the CSTZ substrate. In contrast, sufficient adhesive strength was confirmed in Samples 1 to 4. From this, it was found that when the glass powder used in the conductive paste, as in Samples 1 to 4, is a glass powder having a composition according to the present disclosure, sufficient adhesive strength can be obtained with respect to the CSTZ substrate. On the other hand, no adhesive strength was obtained with respect to the pellets obtained from the conductive pastes of Samples 8 to 12. This is considered to be because the composition of the glass powder used in the conductive pastes of Samples 8 to 12 was outside the range of the present disclosure.

[0090] 2-1. Examination of adhesive strength due to differences in baking temperature In order to further evaluate the adhesive performance of the glass powder of the present disclosure, in this test, the adhesive strength of the evaluation pastes of Sample 1 and Sample 2 at different firing temperatures was examined. Specifically, first, pellets and a CSTZ substrate of Sample 1 were prepared in the same manner as above. Then, a test piece in which a fired film was formed on a CSTZ substrate was obtained in the same manner as in 1-1 above, except that the firing temperature was set to 710°C. An adhesive strength test was performed on the test piece in the same manner as above. In addition, pellets and a CSTZ substrate were prepared under the same conditions for Sample 2, and an adhesive strength test was performed under the same conditions as for Sample 1. The results are shown in Table 2.

[0091] [Table 2]

[0092] As shown in Table 2, it was confirmed that good adhesive strength was obtained for Sample 1 even when the pellets were fired at 710°C. Similarly, good adhesive strength was obtained for Sample 2 when fired at 710°C.

[0093] 2-2. Examination of adhesive strength on barium titanate substrate (BT substrate) In this test, the adhesive strength of the glass powders according to Sample 1 and Sample 2 to the BT substrate was examined. Specifically, first, the pellets according to Sample 1 were prepared by the same method as above. Next, a mixture of barium titanate powder and a binder was press-molded and fired at 1300°C for 2 hours in an air atmosphere. This prepared a flat barium titanate substrate (hereinafter referred to as the BT substrate) with dimensions of 26mm x 26mm x 1.3mm. Then, the pellets according to Sample 1 were placed on the BT substrate, and a firing process was performed for 30 minutes in a nitrogen atmosphere. This resulted in a test piece. In order to evaluate the adhesive strength for each firing temperature, test pieces were prepared by firing the above at 730°C or 710°C. The test pieces were subjected to an adhesive strength test in the same manner as above. In addition, pellets and a BT substrate were prepared under the same conditions for Sample 2, and an adhesive strength test was performed under the same conditions as for Sample 1. The results are shown in Table 3.

[0094] [Table 3]

[0095] As shown in Table 3, even when the adhesive strength test was performed using the BT substrate instead of the CSTZ substrate, it was confirmed that good adhesive strength was obtained for both Sample 1 and Sample 2. From the viewpoint of firing temperature, it was confirmed that good adhesive strength was obtained even when the BT substrate was fired at 710°C.

[0096] 3. Scratch Evaluation Here, in order to further evaluate the properties of the glass powder of the present disclosure, the glass powders according to Samples 1, 4 to 5, and 12 were evaluated by a scratch test.

[0097] (1) Preparation of conductive paste for evaluation First, a conductive paste for evaluation was prepared. Specifically, a conductive paste containing 74 wt% conductive particles (median diameter D 50Conductive pastes were prepared by mixing 8 wt% of glass powder (4 μm plate-like Cu particles) for samples 1, 4 to 5, and 12, 5 wt% of binder (acrylic resin, molecular weight 150,000 to 200,000), 12.7 wt% of dispersion medium (dihydroterpineol), and 0.3 wt% of dispersant (carboxylic acid dispersant). Thus, conductive pastes for evaluation for samples 1, 4 to 5, and 12 were obtained.

[0098] (2) Formation of electrodes for evaluation First, a laminated chip (a laminated ceramic capacitor body) in which a dielectric layer mainly composed of CSTZ and an internal electrode of 0402 size were laminated was prepared. The conductive paste for evaluation of Sample 1 was applied to the part where the internal electrode was exposed on the end face of the laminated chip. The dip coating method was used to apply the paste. After that, a drying process was performed at 120°C for 10 minutes using a hot air dryer. Then, a firing process was performed on the formed dried film. The firing time was set to 10 minutes, and the total processing time including the temperature rise time (the time from the start of firing to the end of firing) was set to 1 hour. The firing atmosphere was set to a nitrogen atmosphere. In this evaluation, in order to examine the difference in scratch strength of the external electrode depending on the firing temperature, the firing temperature of the dried film was changed to 700°C, 715°C, 730°C, and 750°C for each sample, and the evaluation electrodes were prepared. In this way, an evaluation electrode was prepared in which the conductive paste for evaluation of Sample 1 was formed on the surface of the laminated chip as an external electrode. In addition, for Samples 4, 5 and 12, electrodes for evaluation were formed under similar conditions.

[0099] (3) Scratch test The scratch strength (scratch resistance) of the external electrode was evaluated for the evaluation electrode obtained above under a room temperature environment. After the test, the state of the external electrode was observed with an optical microscope. FIG. 2 is a photograph of the evaluation electrode formed using Sample 1 after the scratch test. FIG. 3 is a photograph of the evaluation electrode formed using Sample 4 after the scratch test. FIG. 4 is a photograph of the evaluation electrode formed using Sample 5 after the scratch test. FIG. 5 is a photograph of the evaluation electrode formed using Sample 12 after the scratch test. The bright parts in the upper half of FIG. 2 to FIG. 5 show the external electrode formed on the substrate, and the dark parts show that the external electrode has peeled off (damaged) from the substrate.

[0100] As shown in Figures 4 and 5, significant peeling of the external electrodes after the scratch test was observed in the external electrodes obtained by firing Sample 5 and Sample 12. On the other hand, as shown in Figures 2 and 3, it was confirmed that the external electrodes of Sample 1 and Sample 4 were less susceptible to peeling compared to Sample 5 and Sample 12, regardless of the firing temperature at which they were fired. This also demonstrated that the external electrodes of Sample 1 and Sample 4 have good scratch strength against the multilayer chip (multilayer ceramic capacitor body).

[0101] Although the technology disclosed herein has been described in detail above, these are merely examples, and various modifications can be made to the present disclosure without departing from the spirit and scope of the present disclosure. [Explanation of symbols]

[0102] 1. Multilayer ceramic capacitors (MLCCs) 10 Stacked Chip 20 Dielectric layer 30 Internal electrode layer 40 External electrode

Claims

1. A glass powder used in a conductive paste, The glass powder has the following composition in terms of oxide mass ratio: SiO 2 :6wt%~18wt%; B 2 O 3 :18wt%~30wt%; ZnO: 26wt% to 47wt%; <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :2wt%~17wt%; CaO: 10wt% to 25wt%; and is substantially free of BaO; Glass powder.

2. The glass powder of claim 1 , wherein the glass powder is substantially free of alkaline earth metal oxides other than CaO.

3. The glass powder according to claim 1 , wherein the softening point of the glass powder is 500° C. or more and 650° C. or less.

4. The median diameter D of the glass powder 50 The glass powder according to claim 1 , wherein the average particle size is 1 μm or more and 3 μm or less.

5. The glass powder is B 2 O 3 The glass powder according to claim 1 , comprising 20 wt % or more of

6. The glass powder contains Al in terms of oxide. 2 O 3 The glass powder according to claim 5 , comprising 10 wt % or more of

7. A glass powder according to any one of claims 1 to 3, conductive particles, and a dispersion medium. Conductive paste.

8. The conductive paste according to claim 7 , wherein the conductive particles are Cu particles.

9. 8. The conductive paste according to claim 7, wherein the glass powder is contained in an amount of 4 wt % to 12 wt % when the entire conductive paste is taken as 100 wt %.

10. A paste preparation step of preparing a conductive paste containing glass powder, conductive particles, and a dispersion medium; a laminated chip preparation step of preparing a laminated chip; a paste applying step of applying the conductive paste prepared in the paste preparing step to a surface of the laminated chip prepared in the laminated chip preparing step; a firing step of firing the laminated chip to which the conductive paste is applied; A method for producing a multilayer ceramic capacitor, comprising: The glass powder has the following composition in terms of oxide mass ratio: SiO 2 :6wt%~18wt%; B 2 O 3 :18wt%~30wt%; ZnO: 26wt% to 47wt%; <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :2wt%~17wt%; CaO: 10wt% to 25wt%; and is substantially free of BaO; A method for manufacturing a multilayer ceramic capacitor.

11. The laminated chip includes a dielectric layer mainly composed of a perovskite oxide. The method for producing a multilayer ceramic capacitor according to claim 10.

12. The perovskite oxide is (CaSr)(TiZr)O 3 Including, The method for producing a multilayer ceramic capacitor according to claim 11.

13. The firing step is carried out at a firing temperature of 650° C. or more and 850° C. or less. The method for producing a multilayer ceramic capacitor according to claim 10 or 11.

Citation Information

Patent Citations

  • Dielectric compositions

    JP1978082825A

  • Disc recording / Reproducing apparatus

    JP1996017140A

  • Conductive paste

    JP1997306236A

  • Manufacture of plasma display panel

    JP2000156165A

  • Ceramic multilayer component

    JP2009152489A